PENENTUAN DAERAH “MODIFIED ATMOSPHERE” (MA) UNTUK PENYIMPANAN BUAH SALAK PONDOH SEGAR - Gunadnya, Ida Bagus Putu (Universitas Udayana, 2009)
MA storage combined with cold storage has been wellknown for its advantages in storing fresh produces. So, inthis research an attempt was carried out to determine the MAof fresh Pondoh snake fruit. Two levels of low O2 concentrationswhich combined with four levels of high CO2 wereapplied to find out the proper MA storage for the fresh fruitat temperature of 10 and 15oC. A storage of the fruit atnormal atmosphere was also made as a control. Qualitymeasurements were done on hardness and colour of the fruitpulp.Experiments showed that only four O2 – CO2 combinationsthat gave better fruit responses, when the fruit wasstored for 18 days at 10 and 15oC. So, it was suggested thatthe MA storage of fresh Pondoh snake fruit was at 4 ± 2% O2with 14 ± 4 CO2 for 18 days storage at 10 and 15°C.